Virtual Reality and its Applications in China: An Overview - Pan, Zhigeng; Shi, Jiaoying; Lu, Qin (International Journal of Virtual Reality, 2000)
Nowadays Virtual Reality (VR) has become a hot research topic. In China researchers have obtained a lot of achievements in various VR fields. VR is no longer limited to academic research as it used to be, it has sprung up to a new industry. This paper gives an overview of the research and development on VR in China, including the mainland of China, Hong Kong and Macao. It also gives a summary of the 11 selected papers in the printed edition of this and the next special issues.